Respiratory disturbances in a mouse model of Parkinson's disease. Issue 5 (7th March 2019) - Oliveira, Luiz M.; Oliveira, Maria A.; Moriya, Henrique T.; Moreira, Thiago S.; Takakura, Ana C.
Abstract : New Findings: What is the central question of this study? Clinical reports have described and suggested central and peripheral respiratory abnormalities in Parkinson's disease (PD) patients; however, these reports have never addressed the occurrence of these abnormalities in an animal model. What is the main finding and its importance? A mouse model of PD has reduced neurokinin‐1 receptor immunoreactivity in the pre‐Bӧtzinger complex and Phox2b‐expressing neurons in the retrotrapezoid nucleus. The PD mouse has impairments of respiratory frequency and the hypercapnic ventilatory response. Lung collagen deposition and ribcage stiffness appear in PD mice. Abstract: Parkinson's disease (PD) is a neurodegenerative motor disorder characterized by dopaminergic deficits in the brain. Parkinson's disease patients may experience shortness of breath, dyspnoea, breathing difficulties and pneumonia, which can be linked as a cause of morbidity and mortality of those patients. The aim of the present study was to clarify whether a mouse model of PD could develop central brainstem and lung respiratory abnormalities. Adult male C57BL/6 mice received bilateral injections of 6‐hydroxydopamine (10 μg μl −1 ; 0.5 μl) or vehicle into the striatum. Ventilatory parameters were assessed in the 40 days after induction of PD, by whole‐body plethysmography. In addition, measurements of respiratory input impedance (closed and opened thorax) were performed. 6‐Hydroxydopamine reduced the number of tyrosine hydroxylase neurons in the substantia nigra pars compacta, the density of neurokinin‐1 receptor immunoreactivity in the pre‐Bӧtzinger complex and the number of Phox2b neurons in the retrotrapezoid nucleus. Physiological experiments revealed a reduction in resting respiratory frequency in PD animals, owing to an increase in expiratory time and a blunted hypercapnic ventilatory response. Measurements of respiratory input impedance showed that only PD animals with the thorax preserved had increased viscance, indicating that the ribcage could be stiff in this animal model of PD. Consistent with stiffened ribcage mechanics, abnormal collagen deposits in alveolar septa and airways were observed in PD animals. Our data showed that our mouse model of PD presented with neurodegeneration in respiratory brainstem centres and disruption of lung mechanical properties, suggesting that both central and peripheral deficiencies contribute to PD‐related respiratory pathologies. Abstract :